Degradação e vulnerabilidade ambiental: um estudo sobre o ribeirão pira no povoado passarinho - Souza, Elia Gomes de (Universidade Federal do Tocantins, 2019)
With the growth of urbanization, vegetation and springs have been destroyed throughout Brazil, and with this, rational and irrational beings are being harmed, since vegetation as well as water resources is the most important part of the balance of life in the Earth. The objective of this work is to understand the causes that led to the destruction of the gallery forests of the Pira stream, in Passarinho, Tocantinópolis - OT municipality. This research, besides dealing with the deforestation of gallery forests in the Pira stream, also shows the importance of preserving the environment. Also the textual discussion here, seeks to encourage people to align themselves with education and environmental awareness to act consistently in the defense of the environment. The research shows that it is of utmost importance to take care of the gallery forests of the streams and not to destroy them, and when necessary, to restore the forests that were once devastated. This analysis was elaborated from a field research, where we adopted as method of a qualitative research based on the experiences of the elders of the community.